Principles-Based Budgeting: Resources for Revisioning Academic Planning - Carter, Dante; Jaisee, Tasnim; Nickel, Lorelei; Kalagnanam, Suresh (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
In working toward a budgeting framework that responds to the often harmful impacts of neoliberal accounting practices on people and places, this research has been guided by deep-rooted principles that were gifted to the University of Saskatchewan, through a rigorous Indigenous-led community consultation process which interpreted institutional strategic principles, using Cree and Michif terms: nākatēyihtamowin | nakaatayihtaamoowin (sustainability), nihtāwihcikēwin | nihtaooshchikaywin (creativity), nanātohk pimātisowina | nanaatoohk pimatishoowin (diversity), and āniskōmohcikēwin | Naashkoopitamihk (connectivity). This consultation demonstrated the pressing need to redefine what a successful budgeting framework might mean by looking beyond the role of a financial plan and adopting a more broad-based approach using socially and environmentally responsible lenses that incorporate new directions based on Indigenous knowledges, world views, and values invested in creating a more inclusive and productive campus in targeted, incremental, and structural ways. This exploratory study builds on information gathered internally from the university’s student governance structures, broad conversations within an ad hoc advisory group, and relevant literature. An important role of budgeting is that it can guide performance measurement and management; our exploration included looking for ways to identify potentially “new-old” measurements of success as they pertain to the university’s stated objectives and aspirational goals. Current challenges of resource allocation faced by the university were reviewed to identify bottlenecks based on funding limitations that cause barriers to accessibility to academic and non-academic supports, and undesirable environmental effects. Our study raises more questions than answers, but provides insight into potential future processes, which we anticipate in this field report.